Cardiac pH-Imaging With Hyperpolarized MRI - Bøgh, Nikolaj; Hansen, Esben Søvsø Szocska; Mariager, Christian Østergaard; Bertelsen, Lotte Bonde; Ringgaard, Steffen; Laustsen, Christoffer (Frontiers in Cardiovascular Medicine, 2020)
Regardless of the importance of acid-base disturbances in cardiac disease, there are currently no methods for clinical detection of pH in the heart. Several magnetic resonance imaging techniques hold translational promise and may enable in-vivo mapping of pH. We provide a brief overview of these emerging techniques. A particular focus is on the promising advance of magnetic resonance spectroscopy and imaging with hyperpolarized 13C-subtrates as biomarkers of myocardial pH. Hyperpolarization allows quantification of key metabolic substrates and their metabolites. Hereby, pH-sensitive reactions can be probed to provide a measure of acid-base alterations. To date, the most used substrates are [1-13C]pyruvate and 13C-labelled bicarbonate; however, others have been suggested. In cardiovascular medicine, hyperpolarized magnetic resonance spectroscopy has been used to probe acid-base disturbances following pharmacological stress, ischemia and heart failure in animals. In addition to pH-estimation, the technique can quantify fluxes such as the pivotal conversion of pyruvate to lactate via lactate dehydrogenase. This capability, a good safety profile and the fact that the technique is employable in clinical scanners have led to recent translation in early clinical trials. Thus, magnetic resonance spectroscopy and imaging may provide clinical pH-imaging in the near future.